Effect of exercise-induced muscle damage on vascular function and skeletal muscle microvascular deoxygenation - Caldwell, J. T.; Wardlow, G. C.; Branch, P. A.; Ramos, M.; Black, C. D.; Ade, Carl J. (My University, 2017)
This paper investigated the effects of unaccustomed eccentric exercise-induced muscle damage (EIMD) on macro-and microvascular function. We tested the hypotheses that resting local and systemic endothelial-dependent flow-mediated dilation (FMD) and microvascular reactivity would decrease, (V) over dotO(2max) would be altered, and that during ramp exercise, peripheral O-2 extraction, evaluated via near-infrared-derived spectroscopy (NIRS) derived deoxygenated hemoglobin + myoglobin ([HHb]), would be distorted following EIMD. In 13 participants, measurements were performed prior to (Pre) and 48 h after a bout of knee extensor eccentric exercise designed to elicit localized muscle damage (Post). Flow-mediated dilation and postocclusive reactive hyperemic responses measured in the superficial femoral artery served as a measurement of local vascular function relative to the damaged tissue, while the brachial artery served as an index of nonlocal, systemic, vascular function. During ramp-incremental exercise on a cycle ergometer, [HHb] and tissue saturation (TSI%) in the m. vastus lateralis were measured. Superficial femoral artery FMD significantly decreased following EIMD (pre 6.75 +/- 3.89%; post 4.01 +/- 2.90%; P < 0.05), while brachial artery FMD showed no change. The [HHb] and TSI% amplitudes were not different following EIMD ([HHb]: pre, 16.9 +/- 4.7; post 17.7 +/- 4.9; TSI%: pre, 71.0 +/- 19.7; post 71.0 +/- 19.7; all P > 0.05). At each progressive increase in workload (i.e., 0-100% peak), the [HHb] and TOI% responses were similar pre-and 48 h post-EIMD (P > 0.05). Additionally, (V) over dotO(2max) was similar at pre-(3.0 +/- 0.67 L min(-1)) to 48 h post (2.96 +/- 0.60 L min(-1))-EIMD (P > 0.05). Results suggest that moderate eccentric muscle damage leads to impaired local, but not systemic, macrovascular dysfunction.
Citation: Caldwell, J. T., Wardlow, G. C., Branch, P. A., Ramos, M., Black, C. D., & Ade, C. J. (2016). Effect of exercise-induced muscle damage on vascular function and skeletal muscle microvascular deoxygenation. Physiological Reports, 4(22), 12. doi:10.14814/phy2.13032
Keywords: Flow-Mediated Dilation; Muscle Damage; Near-Infrared Spectroscopy; Vascular Function; Near-Infrared Spectroscopy; Flow-Mediated Dilation